(untitled) (Journal of Comparative & International Higher Education, 2022)
Increased international students could potentially contribute to the institutional financial stability. However, there is limited research evidence regarding the association between net tuition revenue and international undergraduate student enrollment at public doctoral universities through a longitudinal perspective. This research, therefore, fills the gap and investigates the association between international student enrollment and the financial status of institutions. Informed by Cost-Benefit Analysis (CBA), this study used correlational analysis, One-way ANOVA and Post Hoc tests to examine the relationship from different perspectives. These findings indicated a statistically significant positive correlation between net tuition revenue and international undergraduate student enrollment numbers at public doctoral universities from 2000 and 2018. The research also revealed statistically significant differences in net tuition revenue among institutions grouped by international undergraduate student enrollment levels. The results illustrated the nuanced trend in the three waves of international student enrollment.